Intraoral approach for treatment of displaced condylar fractures: case report - Pereira-Filho, Valfrido [UNESP]; Welsh, Bärbel; Schübel, Florian; Landes, Constantin; Sader, Robert; Gabrielli, Mário Francisco Real [UNESP]; Monnazzi, Marcelo (MDPI, 2011)
Dislocated subcondylar fractures often require open reduction and internal fixation. This treatment modality results in better anatomy, early function, and facilitated physical therapy. Ideal stable fixation is obtained by use of two miniplates to control the tension zone in the sigmoid notch area and stabilize the posterior border region or, if there is not enough space, one stronger plate. That is most frequently achieved through extraoral approaches. Recently new instruments have facilitated the use of an intraoral approach, which is used usually with the aid of an endoscope. However, it is possible to perform the procedure without the endoscope if proper instruments and clinical mirrors for checking the posterior border reduction and fixation are used. A case of reduction and fixation of a medially dislocated condylar fracture is presented and discussed.
Keywords: Subcondylar fracture; Intraoral; Surgical approach